The genetic architecture of cervical length is shared with spontaneous preterm birth risk - Hope M. Wolf; Bradley T. Webb; Jerome F. Strauss; Adi L. Tarca; Roberto Romero; Sonia S. Hassan; Shawn J. Latendresse; Tinnakorn Chaiworapongsa; Stanley Berry; Nardhy Gomez-Lopez; Piya Chaemsaithong; Timothy P. York (Communications Medicine)
Abstract Background Sonographic cervical length is a powerful predictor of maternal risk for spontaneous preterm birth (sPTB). Twin and family studies have established a maternal genetic heritability for sPTB ranging from 13 to 20%, however, there is no corresponding estimate for the heritability of mid-trimester cervical length, or an understanding of how genetic factors contribute to cervical changes across pregnancy. Methods This study was based on a prospective longitudinal cohort of (N = 5,160) Black/African American women who underwent serial sonographic examination of the uterine cervix during pregnancy and were genotyped via next-generation low-pass whole genome sequencing. Results Bivariate genetic correlations estimated using genome-wide complex trait analysis (GCTA) indicated that a large proportion of the genes influencing cervical change across pregnancy also influenced gestational duration. SNP-level associations were observed near genes involved in the progesterone, estrogen, and insulin signaling pathways. Conclusions These results suggest that a large proportion of genetic loci for preterm birth exert their influence through the process of cervical remodeling. Polygenic profiling of maternal genetic liability to cervical shortening could aid in the development of clinical risk assessment tools to identify high-risk women who may benefit from more frequent cervical length screening and earlier interventions to prevent preterm delivery.